(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Silver nanoparticles (AgNPs) have demonstrated numerous physicochemical, biological, and functional properties suitable for biomedical applications, including anticancer and drug carrier properties. In the present study, the antibiotic, Levofloxacin (Levo), was loaded onto AgNPs, which were synthesized via the chemical reduction method, and evaluated as antioxidants and anticancer agents. The characterized XRD and FE-SEM analyses were 10-40 nm. The antioxidant potentials of AgNPs and their conjugates, tested via their 1,1-diphenyl-2-picryl-hydrazyl (DPPH) scavenging ability Overall, according to the results obtained in the present study, the new nanocomposite, AgNPs-Levo, showed the highest antioxidant activity and anti-cancer activity. The preparation has high clinical potential for prospective use as an Anticancer agent.